Turkish University Students’ Perceptions of the World Wide Web as a Learning Tool: An Investigation Based on Gender, Socio-Economic Background, and Web Experience - Tekinarslan, Erkan (International Review of Research in Open and Distributed Learning, 2009)
The main purpose of the study is to investigate Turkish undergraduate students’ perceptions of the Web as a learning tool and to analyze whether their perceptions differ significantly based on gender, socio-economic background, and Web experience. Data obtained from 722 undergraduate students (331 males and 391 females) were used in the analyses. The findings indicated significant differences based on gender, socio-economic background, and Web experience. The students from higher socio-economic backgrounds indicated significantly higher attitude scores on the self-efficacy subscale of the Web attitude scale. Similarly, the male students indicated significantly higher scores on the self-efficacy subscale than the females. Also, the students with higher Web experience in terms of usage frequency indicated higher scores on all subscales (i.e., self-efficacy, affective, usefulness, Web-based learning). Moreover, the two-way ANOVA results indicated that the student’s PC ownership has significant main effects on their Web attitudes and on the usefulness, self-efficacy, and affective subscales.